Effect of Duration of Exposure of Thumb Movements While Operating Mobile Phone on Nerve Conduction Velocity and Handgrip Strength in Undergraduate Medical Students - Jagdish C. Hundekari; Sanjay Wasnik; Manoj Paliwal; Indrajeet Yadav; Chandeep Kau; Bhumika Badjatiya; Lokendra Kot; Ranjana Sharma (Journal of Pharmacy and Bioallied Sciences)
Introduction: Use of mobile phones has clearly been increased in recent times with all the developing technologies, attracting the younger generation to use them which may lead to addiction. Students these days are continuously engaged in their mobile phones chatting with each other or probably playing games like PubG. Aims and Objective: In the present study, we investigated the handgrip strength and median motor nerve conduction velocity to assess the impact of duration of mobile usage on the functional status of the hands. Material and Method: 175 undergraduate medical students aged 18–25 years were divided into four groups depending on duration of usage: less than 1 year (N = 23), 1–2 years (N = 89), 2–4 years (N = 37), and more than 4 years (N = 26). Median motor nerve conduction velocity and grip and pinch strengths were recorded. Results: Significantly lower median motor nerve conduction velocity was observed as the duration of smartphone usage increased (P < 0.0005). Handgrip strength was reduced non-significantly as duration of smartphone use increased (P < 0.224). Conclusion: Smartphone overuse reduces the nerve conduction velocity and decreases handgrip strength and hand functions which may increase the risk of peripheral neuropathy.